Heat and mass transfer effects on an unsteady MHD boundary layer flow of fractionalized fluid - Shafique A.; Ramzan M.; Amir M.; Abbas S.; Nazar M.; Ali E.; Alharthi A.M.; Jan R.; Garalleh H.A.L. (Taylor and Francis Ltd., 2025)
This research investigates the transient magnetohydrodynamic (MHD) flow of a non-integer Maxwell fluid over a vertical plate, taking into account the effect of diffusion-thermo and parameter of heat absorption. The fractional derivative Caputo-Fabrizio is employed to model the problem. Using the Laplace integral transform technique, we solve the dimensionless governing equations to obtain the profiles of velocity, concentration, and temperature, which are then presented in graphical form for easy comparison and interpretation. The influence of several parameters?specifically, the fractional parameter and heat absorption is thoroughly analyzed and illustrated through a series of graphical representations. Furthermore, a comparison between traditional as well as fractionalized velocity fields is provided. The results show that chemical reactions and magnetic fields reduce the velocity profile, while diffusion-thermo and mass Grashof number increase the fluid velocity. ? 2024 Informa UK Limited, trading as Taylor & Francis Group.